2022
DOI: 10.3389/fpsyt.2022.877574
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical Affective Touch Therapy for Anxiety Disorders: Feasibility, Clinical Outcomes, and Electroencephalography Biomarkers From an Open-Label Trial

Abstract: BackgroundMost external peripheral nerve stimulation devices designed to alter mood states use electrical energy, but mechanical stimulation for activation of somatosensory pathways may be harnessed for potential therapeutic neuromodulation. A novel investigational device for Mechanical Affective Touch Therapy (MATT) was created to stimulate C-tactile fibers through gentle vibrations delivered by piezoelectric actuators on the bilateral mastoid processes.Methods22 adults with anxiety disorders and at least mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…The applied stimulation through mechanical affective touch therapy has CT fibers as its target. Electroencephalography studies revealed that the treatment also led to increased occipital theta and alpha oscillatory activity [116]. Interestingly, alpha oscillatory activity seems to be correlated with interoceptive awareness and a relaxing state, whereas an increase in theta oscillation is associated with a mindful state.…”
Section: Touch As Therapy?mentioning
confidence: 96%
“…The applied stimulation through mechanical affective touch therapy has CT fibers as its target. Electroencephalography studies revealed that the treatment also led to increased occipital theta and alpha oscillatory activity [116]. Interestingly, alpha oscillatory activity seems to be correlated with interoceptive awareness and a relaxing state, whereas an increase in theta oscillation is associated with a mindful state.…”
Section: Touch As Therapy?mentioning
confidence: 96%